Effects of ethanol and acetic acid on the transport of malic acid and glucose in the yeast Schizosaccharomyces pombe: implications in wine deacidification - Sousa, Maria João (1995)
Ethanol and acetic acid, at concentrations which may occur during wine-making, inhibited the transport of ι-malic acid in Schizosaccharomyces pombe. The inhibition was non-competitive, the decrease of the maximum initial velocity following exponential kinetics. Glucose transport was not significantly affected either by ethanol (up to 13%, w/v) or by acetic acid (up to 1.5%, w/v). The uptake of labelled acetic acid followed simple diffusion kinetics, indicating that a carrier was not involved in its transport. Therefore, the undissociated acid appears to be the only form that enters the cells and is probably responsible for the toxic effects. Accordingly, deacidification by Ss. pombe during wine fermentation should take place before, rather than after, the main alcoholic fermentation by Saccharomyces cerevisiae.